Education First! From Martin Luther to Sustainable Development - Lutz, Wolfgang (African Sun Media, 2017)
"This scholarly yet highly accessible volume by two renowned experts shows why education is under threat, and what should be done to counter this. The authors mobilise a fascinating array of compelling historical and current evidence which demonstrates the centrality of education to the creation of flourishing societies and show the dire consequences of its neglect. Anyone interested in education and development should read this book." - Professor Ian Goldin, University of Oxford